Environmental Health Risk Analysis of Mercury (Hg) Heavy Metal Exposure (Study on People Consuming Milkfish Around Konawe Industrial Area) - Abubaeda, Dewi Yulianty; Jayadipraja, Erwin Azizi; Harun, Abdul Azis (Waluya The International Science of Health Journal, 2023)
Background: Industrial activities of mining material processing have the potential to cause water pollution. Activities in the Konawe Industrial Estate also require a Steam Power Plant, which has the potential to produce mercury metal (Hg) sourced from coal as raw material. This study aims to analyse the environmental health risks of Hg heavy metal exposure in people who consume milkfish from the Konawe Regency industrial area. Methods: This type of research is quantitative research with Field Research and Laboratory Research methods. The population in this study consisted of 2 subjects, namely people living in the Konawe Industrial Estate area and milkfish specimens. Community samples totaled 97 people and specimen samples were taken at 4 pond locations. Data analysis using Environmental Health Risk Assessment (ERA). Results: The results of the study obtained the average concentration of mercury heavy metal (Hg) in milkfish was 0.003 mg / kg, the large intake of respondents in consuming milkfish for mercury heavy metal (Hg) was 0.00891 mg / kg / day, and the level of risk of respondents and pollution based on the RQ calculation value was still < 1 . Conclusion: People who consume milkfish from the Konawe Industrial Estate do not have a risk of health problems for now and in the next 30 years. Risk management to prevent the emergence of risks is to maintain the rate of intake and frequency of exposure.